Análisis del comportamiento de las exportaciones en Loreto de productos no tradicionales peces ornamentales 2017 - 2021 - Soplin Flores, Marielena (2022)
The research entitled "Analysis of the behavior of exports in Loreto of non-traditional ornamental fish products 2017 - 2021" aims to analyze the evolution of Loreto exports of non-traditional ornamental fish products, period 2017 - 2021. The study is focused quantitative, descriptive level, non-experimental design, having as study population, all statistical records related to Loreto exports of non-traditional ornamental fish products in the Period 2017 - 2021, which exist in the National Superintendence of Tax Administration and the design is non-experimental with longitudinal cost. The investigation concluded by showing that the evolution of exports is cyclical, it grew from 2017 to 2019 and in 2020 it decreased due to the Covid 19 pandemic, recovering slightly in 2021, in addition there are few companies that carry out exports as well as few destination countries.